Pharmacokinetic Studies in Elasmobranchs: Meloxicam Administered at 0.5 mg/kg Using Intravenous, Intramuscular, and Oral Routes to Nursehound Sharks (Scyliorhinus stellaris) - Morón-Elorza, Pablo; Rojo-Solís, Carlos; Álvaro-Álvarez, Teresa; Valls-Torres, Mónica; García-Párraga, Daniel; Encinas, Teresa (Frontiers in Veterinary Science, 2022)
Infectious and inflammatory diseases are the most frequently diagnosed pathologies in elasmobranchs maintained under human care. Non-steroidal anti-inflammatory drugs (NSAIDs) are frequently used in veterinary medicine for their anti-inflammatory, analgesic, and antipyretic properties. Meloxicam is a commonly prescribed NSAID in elasmobranchs, but there are still no published pharmacokinetic (PK) studies supporting its use in this group of animals. In this study, meloxicam was administered at a single dose of 0.5 mg/kg to eight healthy adult large-spotted catsharks (Scyliorhinus stellaris) intravenously (IV), intramuscularly (IM), and orally (PO), with a minimum four-week washout period between administrations. Blood samples were obtained both beforehand and at predetermined times after each administration. Plasma concentrations were measured using a validated high-performance liquid chromatography method, and PK data was obtained using non-compartmental analysis. Meloxicam administered orally did not produce detectable concentrations in blood plasma, while mean peak plasma concentration was 0.38 ± 0.08 µg/ml after IM administration. The mean terminal half-life was 10.71 ± 2.77 h and 11.27 ± 3.96 h for IV and IM injections, respectively. The area under the curve extrapolated to infinity was 11.37 ± 2.29 h·µg/ml after IV injections and 5.98 ± 0.90 h·µg/ml after IM injections. Meloxicam administered IM had a mean absolute bioavailability of 56.22 ± 13.29 %. These numbers support meloxicam as a promising drug to be used IM in catsharks, questions the efficacy of its single PO use in elasmobranchs, elucidate the need for higher dosage regimes and evidence the need for further PK studies in sharks and rays.